Factors mediating work-family balance to job satisfaction in higher education during pandemic - Made Rai, Ni Gusti; Ratu, Aurelius; Savitri, Eka Dian (Indigenous, 2021)
Abstract. The covid-19 pandemic has had an impact on the family and work domains and has forced married employees to adapt to the new condition and strive to achieve the workplace’s established goals. However, given the health risk involved in this situation, can they be satisfied with their job? This question arose because some studies showed that flexibility and more incentive payments were considered to support job commitment, and therefore job satisfaction. Thus, our main concern is whether job satisfaction can becompensated solely through incentive payment, which is economics. Although job satisfaction is intended to measure the quality of employment, those studies presumably amplified the imbalance between work and family relationships. This current study investigates job satisfaction for married employees by highlighting the family domain and exploring the intervening factors that play significant roles during the pandemic.The results of multiple regression analysis of 264 married employees of (with sig 0.1 or 0.05) and path analysis bring our attention to work aspects that appear to be more worrisome than family concerns. As an effort to monitor the quality of employment, it will be ambiguous if, for the sake of job satisfaction, the organization have to pay more incentive payment for increasing commitment without paying more attention to a broader context of the situation. Practical policy implications of the findings of this study are also discussed.Keywords: family balance; job satisfaction; married employee; work balance